PERANCANGAN SISTEM INFORMASI RESERVASI TEMPAT FUTSAL SECARA ONLINE PADA SINGOSARI FUTSAL SEMARANG BERBASISI WEB MOBILE (Information Technology and Telematics, 2014)
ABSTRACTModernization and current internet-based communication has opened up opportunity for any companies to continue to communicate in developing its business activities. Internet (Interconnected Network) is a global network of computers that are connected to one another, which is able to provide unrestricted access to communication services and information resources.Business activities in the services company, especially internet activities, becomes a very important part for the company itself. Singosari Futsal Semarang is a company provide services of futsal court. Existing reservation system on this company has not been computerized, since it can be seen from the membersregistration system, and reservations of futsal court are still manual.By the new reservation system, it is expected to provide  convenience for consumers in order to register and reserve futsal court which can be accessed via webmobile, supported by rapid, accurate, and relevant tools that fulfill the consumer’s needs. This will make the company easier and faster to get information, promotion, and publicity, so that the consumer interest in services will increase.Keyword : Design, Reservation, Web-Mobile